Plasma membrane calcium ATPase downregulation in dopaminergic neurons alters cellular physiology and motor behaviour in Drosophila melanogaster - Erhardt, Brenda (2021)
The accumulation of Ca2+ and its subsequent increase in oxidative stress is proposed to be involved in selective dysfunctionality of dopaminergic neurons, the main cell type affected in Parkinson's disease. To test the in vivo impact of Ca2+ increment in dopaminergic neurons physiology, we downregulated the plasma membrane Ca2+ ATPase (PMCA), a pump that extrudes cytosolic Ca2+, by expressing PMCARNAi in Drosophila melanogaster dopaminergic neurons. In these animals, we observed major locomotor alterations paralleled to higher cytosolic Ca2+ and increased levels of oxidative stress in mitochondria. Interestingly, although no overt degeneration of dopaminergic neurons was observed, evidences of neuronal dysfunctionality were detected such as increases in presynaptic vesicles in dopaminergic neurons and in the levels of dopamine in the brain, as well as presence of toxic effects when PMCA was downregulated in the eye. Moreover, reduced PMCA levels were found in a Drosophila model of Parkinson's disease, Parkin knock-out, expanding the functional relevance of PMCA reduction to other Parkinson's disease-related models. In all, we have generated a new model to study motor abnormalities caused by increments in Ca2+ that lead to augmented oxidative stress in a dopaminergic environment, added to a rise in synaptic vesicles and dopamine levels.